2017
DOI: 10.21873/anticanres.11636
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Small Molecules on β-Catenin and E-Cadherin Expression in HPV16-positive and -negative Squamous Cell Carcinomas

Abstract: All substances, nilotinib, dasatinib, erlotinib and gefitinib have a significant impact on β-catenin and E-cadherin expression in both HPV16-positive and HPV16-negative cells in vitro. Alterations of β-catenin and E-cadherin could provide novel insights for future targeted therapies of head and neck SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Overall, the tested TKIs and everolimus tended to increase FGF1 and FGF2 expression in the studied HPV-negative andpositive cancer cell lines. Previous studies of our group showed that the expression levels of other key signalling proteins involved in cancerogenesis, such as platelet-derived growth factor, vascular endothelial growth factor (VEGF) receptor and β-catenin, were significantly reduced by TKIs (39)(40)(41). The tested TKIs successfully reduced FGF1 expression within the first 24 h in the UMSCC-11A cell line.…”
Section: Discussionmentioning
confidence: 82%
“…Overall, the tested TKIs and everolimus tended to increase FGF1 and FGF2 expression in the studied HPV-negative andpositive cancer cell lines. Previous studies of our group showed that the expression levels of other key signalling proteins involved in cancerogenesis, such as platelet-derived growth factor, vascular endothelial growth factor (VEGF) receptor and β-catenin, were significantly reduced by TKIs (39)(40)(41). The tested TKIs successfully reduced FGF1 expression within the first 24 h in the UMSCC-11A cell line.…”
Section: Discussionmentioning
confidence: 82%
“…Erlotinib, marketed under the brand name Tarceva, is currently used in the oncology clinic as a tyrosine kinase inhibitor, primarily targets the Epidermal Growth Factor Receptor, and has been a front-line treatment for patients with certain types of lung and pancreatic cancers for nearly twenty years [ 83 ]. Erlotinib has previously been found to reduce β-catenin expression in squamous cell carcinoma cell lines [ 84 ] and to decrease S675 phosphorylated β-catenin in endometrial cancer cell lines, causing β-catenin to be destabilized and degraded [ 85 ]. Our data also suggest that Erlotinib can reduce the nuclear localization of β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum soluble E-cadherin levels were found to be associated with disease invasiveness and a poor outcome in several cancers [ 48 ]. Additionally, erlotinib and gefitinib could reduce E-cadherin expression in human papillomavirus 16-positive and -negative cell lines [ 49 ]. Taken together, it is unclear whether high E-cadherin expression leads to high soluble E-cadherin after TKI treatment.…”
Section: Discussionmentioning
confidence: 99%